Metal-Dependent Regulation of ATP7A and ATP7B in Fibroblast Cultures - Lenartowicz, Malgorzata; Moos, Torben; Ogórek, Mateusz; Jensen, Thomas G.; Møller, Lisbeth B. (Frontiers in Molecular Neuroscience, 2016)
Deficiency of one of the copper transporters ATP7A and ATP7B leads to the rare X-linked disorder Menkes Disease (MD) or the rare autosomal disorder Wilson disease (WD), respectively. In order to investigate whether the ATP7A and the ATP7B genes may be transcriptionally regulated, we measured the expression level of the two genes at various concentrations of iron, copper and insulin. Treating fibroblasts from controls or from individuals with MD or WD for 3 and10 days with iron chelators revealed that iron deficiency led to increased transcript levels of both ATP7A and ATP7B. Copper deficiency obtained by treatment with the copper chelator led to a downregulation of ATP7A in the control fibroblasts, but surprisingly not in the WD fibroblasts. In contrast, the addition of copper led to an increased expression of ATP7A, but a decreased expression of ATP7B. Thus, whereas similar regulation patterns for the two genes were observed in response to iron deficiency, different responses were observed after changes in the access to copper. Mosaic fibroblast cultures from female carriers of MD treated with copper or copper chelator for 6-8 weeks led to clonal selection. Cells that express the normal ATP7A allele had a selective growth advantage at high copper concentrations, whereas more surprisingly, cells that express the mutant ATP7A allele had a selective growth advantage at low copper concentrations. Thus, although the transcription of ATP7A is regulated by copper, clonal growth selection in mosaic cell cultures is affected by the level of copper. Female carriers of MD are rarely affected probably due to a skewed inactivation of the X-chromosome bearing the ATP7A mutation.